Her share of blessings women's religions among pagans, Jews and Christians in the Greco - Roman world - Kraemer, Ross Shepard, 1948- (New York, NY Oxford, 1992)
Includes bibliographical references and index.
Keywords: Women -- Mediterranean Region -- Religious Life -- history; Women and religion -- history; Women in Judaism -- history; Women in Christianity -- history -- Early Church ca. 30-600.; Paganism -- Mediterranean region -- history